Kualitas Daging Kancil (Tragulus javanicus) - D Rosyidi; E Gurnadi; R Priyanto; Suryahadi Suryahadi (Faculty of Animal Science, Bogor Agricultural University, 2010)
Lesser mouse deer is a native animal, which is commonly found in the forest of Java and information concerning this animal is still limited. This research explored the quality of lesser mouse deer meat (Tragulus javanicus). Eight lesser mouse deer (four females and four males) were used in quality aspects of lesser mouse deer meat. The physical properties observed were pH, water holding capacity, tenderness, and cooking loss. While the chemical properties observed were proximate analysis, amino acids, fatty acids, cholesterol, and EPA-DHA of the meat. The results showed that meat samples had average of ultimate pH (6.32), water holding capacity (32.82%), tenderness (1.80 kg f/m2), and cooking loss (45.15%). The average meat chemical compositions namely content of water, protein, fat, ash and cholesterol were 76.33%, 21.42%, 0.51%, 1.20%, and 50.00 mg/100 g, respectively. Fatty acids consisted of lauric, miristic, palmitic, stearic, oleic, linoleic, and linolenic acid were in the amount of 1.04% 3.09%, 30.97%, 0.77%, 59.41%, 3.22%, and 1.12%, respectively. The total EPA and DHA was 0.13% and 0.05%. Respectively, the results showed that quality aspects of lesser mouse deer meat had a high ultimate pH, low water holding capacity, tenderness, high cooking loss, and high water content, high protein, low fat and high cholesterol.